KERAGAAN BIOFISIK, SOSIAL DAN PENDAPATAN SERTA KELAYAKAN USAHA TANI TAMBAK SILVOFISHERY DI KECAMATAN SERUWAY, ACEH TAMIANG - iswahyudi, iswahyudi; Rosmaiti, Rosmaiti; Indra, Siti Balqies; Mulyani, Cut (Jurnal Belantara, 2024)
The increase in aquaculture businesses in the coastal areas of Seruway District, Aceh Tamiang Regency, has resulted in high conversion of mangrove forests into ponds. If management is not carried out, it will have an impact on coastal environmental degradation. Therefore, it is necessary to look for a sustainable pond management model. One model is silvofishery. In developing this silvofishery model, biophysical environmental data, social and economic conditions of pond cultivation are needed. The aim of this research is to determine the biophysical, social performance, income level and feasibility of a silvofishery system pond business. The research was conducted using descriptive methods with survey techniques. The research results show that the silvofishery ponds at the research location use a partite pond model. From the analysis of biophysical properties, overall results were obtained, the conditions were suitable for the development of milkfish and tiger prawn cultivation. From social performance, the results showed that silvofishery system pond farmers are still of productive age and have an average pond area of 5 ha. The income obtained from silvofishery system ponds is IDR 19,560,000/ha/year/farmer. Silvofishery pond system If the R/C value is greater than 1, then silvofishery pond farming is worth pursuing.